Flow of viscous nanofluids across a non-linear stretching sheet - PATTNAIK, Pradyumna Kumar; SYED, Shoeb Ahmed; MISHRA, Sujogya; JENA, Swarnalata; ROUT, Sachindar Kumar; MUDULI, Kamalakanta (Journal of thermal engineering, 2023)
This article aims to demonstrate the flow of viscous nanofluid over a non-linear stretching sheet. Considering thermal radiation and dissipative heat in the heat transport phenomenon encourages the flow properties. In generally, nanofluids are employed in heat transfer equip-ment because they improve the thermal characteristics of coolants present in the equipment. Additionally, these fluids possess unique features that have the potential to be applied in a variety of applications, such as pharmaceutical procedures, hybrid power engines, household refrigerators, grinding, and microchips, among others. Consequently, the current model is built to allow for the optimal selection of thermophysical parameters such as conductivity and viscosity, which will enhance the overall effectiveness of the study. Appropriate transfor-mation rules have been used to modify the highly non-linear PDEs into a couple of highly non-linear ODEs. An efficient built-in MATLAB bvp5C algorithm addresses the boundary value problem under consideration. Using the dimensionless parameters assumed in the prob-lem, changes in the velocity as well as the temperature profiles are shown, and rate coefficients, by using numerical simulations are also employed in tabular form. The important outcomes which are exposed in the study are; that the particle concentration is used as a controlling pa-rameter to reduce the nanofluid velocity, whereas it favours enhancing the fluid temperature and the radiating heat along with the coupling parameter due to the inclusion of dissipative heat also encourages to overshoot the temperature profile.